Distraction Osteogenesis-A Review - K, Sushmitha; D, lohith; Vinayaka; Ezhil Annamalai, Manoj; K, Abhinandana; K, Lochana (Journal of Neonatal Surgery, 2025)
As an alternative to many traditional orthognathic surgical treatments, distraction osteogenesis of the craniofacial skeleton has grown in popularity. It involves the gradual separation of bone segments by incremental traction, which results in the production of new bone between their surfaces. Applying controlled traction at the site of surgically created bone disturbance during its healing process is known as distraction osteogenesis. By establishing and sustaining an active region of bone formation in the surgically generated gap, the approach capitalizes on the regenerative potential of bone while directing the mechanical forces primarily away from the location. Both the bone and its envelope lengthen. Ilizarov provided the scientific foundation for this idea in the 1950s and demonstrated that long bones may be lengthened using this technique without the need for a graft material. The fundamental method consists of surgically breaking the malformed bone, inserting the device, resting for five to seven days, and then gradually separating the bony segments by activating them followed by a consolidation period. Hence, the purpose of this article is to review the historic development ,histology, classification and orthodontic implications distraction osteogenesis.